Decentralization and social rights: reflexions around the satisfaction of the right to education in the framework of the decentralization process - Alvites Alvites, Elena (THĒMIS-Revista de Derecho, 2015)
Historically, fundamental rights have not been perceived in their totality with the same degree of enforceability. However, with the contributionsof both the doctrine and the jurisprudence, todayall   fundamental rights, including those with social character, are considered to impose real obligations on the State.In this article, the author shows how the decentralization process has influenced in this phenomenon, with emphasis on the right to education, and presents an analysis regarding the actual situation of this right in our country based on the positive actions that are under the responsibility of the Ministry of Education and the decentralized organisms.